2020
DOI: 10.1142/s1793292020500083
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Binding of Lysozyme with Gold Nanoparticles: Corona Formation and its Correlation with a Naked-Eye-Based Colorimetric Approach

Abstract: The interaction between colloidal gold nanoparticles (AuNPs) and lysozyme (Lyz) has been studied through spectroscopic and microscopic measurements, molecular docking simulation and colorimetric measurements to investigate corona formation and the mechanism, affinity, number of sites and stoichiometry of binding. Molecular docking simulation endorses that, at physiological pH, the interaction between basic NH2 group of arginine and citrate ions is predominant than the interaction between citrate ions and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Because AuNRs display an opposite surface charge than AuNSs and AuNFs, the biomolecules adsorbed onto the surface of the nanoparticles should have different characteristics, such as conformation, molecular weight, and isoelectric point (pI). Proteins with a different pI carry different charges in a given solution that will influence the electrostatic interactions with the surface of the particles [71,72]. Regarding the HD variation, all the AuNPs showed an increase in HD values after being in contact with saliva and urine samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because AuNRs display an opposite surface charge than AuNSs and AuNFs, the biomolecules adsorbed onto the surface of the nanoparticles should have different characteristics, such as conformation, molecular weight, and isoelectric point (pI). Proteins with a different pI carry different charges in a given solution that will influence the electrostatic interactions with the surface of the particles [71,72]. Regarding the HD variation, all the AuNPs showed an increase in HD values after being in contact with saliva and urine samples.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction often referred to as adsorption, can be attributed to electrostatic interactions, hydrophobic interactions, van der Waals' forces, solvation forces, and hydrogen bonding [79]. Some studies revealed the affinity of lysine, arginine, serine, and threonine for citrate ions on the surface of AuNPs [71,82]. It was also found that the first proteins adsorbed on the surface of AuNPs are present in high concentrations and have high association rate constants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus this phytochemical can shed light on how it binds with different target proteins, aiding researchers in understanding the fundamental mode of action of the drug candidate. Ag and Au nanoparticles are also reported to bind to many proteins, such as serum albumin, hemoglobin, lysozyme, etc., showing good binding affinities ( Sen et al, 2011 ; Aich et al, 2020 ; Shahabadi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 The interaction between AuNPs and plasma proteins had been paid significant attention in recent years, such as serum albumin, 3,[8][9][10][11][12][13][14] g-globulin, 8,15 hemoglobin, 16,17 fibrinogen, 8,18 transferrin, 19 histones and insulin. 8 The interaction of AuNPs with lysozyme, 9,[20][21][22][23] papain, 24 yeast alcohol dehydrogenase, 25 a-amylase, 26 cholesterol oxidase enzyme 27 a-thrombin, 28 and chymotrypsin 29 has also been studied. Conversely, much less is known about the interaction of AuNPs with proteins from the digestive system.…”
Section: Introductionmentioning
confidence: 99%